PENERAPAN MEDIA PAPAN PINTAR MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP MINAT BELAJAR SISWA DI KELAS II SEKOLAH DASAR - Eka Nurul Hidayanti; Heny Kusuma Wardani; Hani Prasetyaning Astuti (CV. ADIBA ASIHA AMIRA, 2024)
This study aims to improve learning outcomes of Pancasila and Civics Education (PPKn) in grade II students of SDN Sewulan 02 through the use of ‘Pancasila Smart Board’ media. The method used was Classroom Action Research (PTK) which was carried out in two cycles. In the pre-cycle, the observation results showed that only 30.77% of students achieved learning completeness with an average score of 60, which indicates low performance. After the application of smart board media in cycle I, the percentage of completeness increased to 69.23%, but was still in the ‘Moderate’ category, indicating the need for further improvement. In cycle II, with improvements made based on the reflection of the previous cycle, the percentage of student completeness increased significantly to 92.31%, indicating a category of ‘Very High.’ This increase shows the effectiveness of using smart board media in helping students understand the values of Pancasila more interactively. In addition, this media also increased students' motivation and involvement in the learning process, making them more active and enthusiastic in learning. This creates a more dynamic and fun classroom atmosphere. Thus, this research proves that the use of Pancasila smart board media is a very useful tool in improving Civics learning outcomes, as well as contributing to the development of more interesting and effective learning methods in the classroom. This media can be a useful innovation for learning in lower grades in developing understanding of Pancasila.